Legal Perspectives on Solidarity Crime in Italy. (16th June 2020) - Pusterla, Francesca
Abstract: This article investigates the political and legal dimension of Italian policy management of migratory crises affecting the European Union and member states. It pays particular attention to the tightening of migrant reception measures from 2016 until 2019. In this dynamic, it argues that the 132/18 governmental legislation "Decree‐Law on Immigration and Security" of 2018 (and the Decree‐Law bis of 2019) represents a breakthrough. The article reveals the shift of solidarity crime from a political to a legal dimension. The unprecedented movement of migrants and refugees into the EU has led to widespread claims for a EU common migratory policy based on international cooperation and equitable sharing of responsibilities. As a frontline member state, Dublin III prescribes to Italy responsibilities in rescue, first safe of migrants, and refugee status determination. Italy's migration policy thus conflicts with its prior international legal commitments, and, for this reason, its concrete applicability is highly debated.